Efektivitas Dana Bantuan Operasional Sekolah (BOS) dalam Peningkatan Mutu Pendidikan pada MIN Lumpatan Kabupaten Musi Banyuasin - Fathullah, Fathullah (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The School Operational Assistance (BOS) program aims to free up tuition fees for underprivileged students and provide relief for other students, so that they can get better quality basic education services until they are completed in order to complete 9 years of basic education compulsory education. Through BOS, the level of primary education students will be freed from all kinds of school operational costs. The purpose of this study was to find out the Management of the School Operational Assistance Fund (BOS) in improving the learning process in State MTs 1 and Al-Arkom MTs Palembang. The technical analysis used in this study is a qualitative data analysis technique. While the data collection techniques used are interviews, documentation and observation. The results showed that the effectiveness of the management of Operational Assistance funds in the process of improving the learning process in Palembang 1 MTSN had been running effectively in accordance with the 2007 School Operational Aid published by the Indonesian Ministry of Religion. As for the effective ones, namely the need for the availability of funds, facilities and infrastructure to support teaching and learning activities, human resources, planning activities or programs and the amount of funds that will be used for these activities or programs, activities to use school operational assistance funds to meet school needs, coordination between the school and the KOMITE, oversight of the use of the School Operational Assistance Fund (BOS), the improvement of the quality of education, the achievement of the objectives of the use of BOS funds and the achievement of the main objectives of the BOS funds program. Whereas in MTS Al-Arkom, the management of BOS funds has not been implemented effectively, namely the need for the availability of funds, facilities and infrastructure to support teaching and learning activities, human resources, planning activities or programs and the amount of funds to be used for these activities or programs. the school with the school KOMITE. Keywords: School Operational Assistance (BOS), Learning Process.